Prospective comparison of minimally invasive glaucoma surgery techniques for goniotomy in primary congenital glaucoma: Optimizing intraocular pressure control - Mayor Orezime Atima; Ugbede Idakwo; Ayodele Jacob Orugun; Oyeronke Komolafe; Melchizedek Ignatius Munaje; Eisuke Shimizu; Nakayama Shintaro; Emmanuel Oluwadare Balogun; Emeka John Dingwoke (Elsevier, 2024)
Background: A family of less invasive glaucoma procedures has been developed to provide moderate reductions in intraocular pressure and medication burden in eyes with therapeutic needs that may not warrant the risks associated with trabeculectomy and tube shunt implantation. This study aims to compare the effectiveness and clinical outcomes of pediatric goniotomy using minimally invasive glaucoma surgery techniques to manage primary congenital glaucoma. Materials and methods: Using a computer-generated set of random numbers, the patients were randomized into three groups: Kahook blade group, microvitreoretinal blade group, and 23G needle group. Each group contained 22 eyes. All patients underwent anesthesia for intraocular pressure measurement, corneal diameter evaluation, and fundoscopy. Preoperative intraocular pressure at presentation and postoperative intraocular pressure were recorded during a one-year follow-up period. Outcome measures included decreases in corneal diameter from preoperative size, mean postoperative reduction in intraocular pressure for each minimally invasive glaucoma surgery technique and absence of intraoperative or postoperative complications. Surgical success was defined as a postoperative intraocular pressure of ≤20 mmHg without antiglaucoma medications or reoperation, based on the last recorded intraocular pressure during postoperative follow-up. Results: A total of 66 eyes were diagnosed with primary congenital glaucoma and underwent goniotomy surgeries during the study period in 2022. The majority (89%) were bilateral cases. Among the patients, there were 26 males and 9 females, which makes up an 8: 2 male-to-female ratio, with an average age range of 2 months to 2 years. After a one-year postoperative follow-up, a significant reduction in intraocular pressure was achieved of ≤18 mmHg. In terms of surgical success with minimally invasive glaucoma surgery techniques, goniotomy with a 23-gauge needle had the most postoperative intraocular pressure, followed by the microvitreoretinal blade and the Kahook blade. On average, the 23-gauge needle had a corneal diameter of 13.8 mm, while the microvitreoretinal blade was 13.9 mm and the Kahook blade recorded 14 mm. Conclusions: Goniotomy using minimally invasive glaucoma surgery techniques has been proven to be an effective surgical technique for the management of childhood glaucoma among Nigerian patients. A reduction in postoperative intraocular pressure, corneal diameter, and absence of complications provide clinical evidence of successful glaucoma management and preservation of outcomes of visual function in patients. Level of evidence: Level 1 (Prospective study)